Organizational Values’ Effects on Civil Servants’ Performance: Normative Commitment Mediation and Competence Moderation - Sophan Bayu Ariady; Ika Barokah Suryaningsih; Etty Puji Lestasri (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2026)
This study examines how organizational values influence employee performance through normative commitment and employee competence. The research aims to explain direct, mediating, and moderating relationships among these variables within KPP Pratama Jember. A quantitative explanatory design with saturated sampling was applied to 93 civil servants, and data were analyzed using PLS-SEM. Results show that organizational values significantly improve performance, normative commitment mediates this effect, and competence strengthens the commitment–performance relationship. The findings highlight the importance of value internalization, ethical responsibility, and capability development as strategic drivers to enhance public-sector performance.